2011
DOI: 10.1007/s12522-011-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal integrity and DNA damage in freeze‐dried spermatozoa

Abstract: Freeze-drying technology may one day be used to preserve mammalian spermatozoa indefinitely without cryopreservation. Freeze-dried mouse spermatozoa stored below 4°C for up to 1 year have maintained the ability to fertilize oocytes and support normal development. The maximum storage period for spermatozoa increases at lower storage temperatures. Freeze-drying, per se, may reduce the integrity of chromosomes in freeze-dried mouse spermatozoa, but induction of chromosomal damage is suppressed if spermatozoa are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 122 publications
(153 reference statements)
1
5
0
Order By: Relevance
“…3c ). Results of this study and previous reports 17 , 18 , 20 24 suggest that cryoprotectant protect the cell organelle and not the DNA from mechanical stress. Therefore, if our method (maintaining vacuum in ampoules) is combined with using cryoprotectant, morphological integrity as well as DNA integrity of FD spermatozoa will be protected, thereby increasing the success rate of the offspring from those spermatozoa.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…3c ). Results of this study and previous reports 17 , 18 , 20 24 suggest that cryoprotectant protect the cell organelle and not the DNA from mechanical stress. Therefore, if our method (maintaining vacuum in ampoules) is combined with using cryoprotectant, morphological integrity as well as DNA integrity of FD spermatozoa will be protected, thereby increasing the success rate of the offspring from those spermatozoa.…”
Section: Discussionsupporting
confidence: 77%
“…For example, Tardigrades can survive under extreme dehydration conditions because of the accumulation of large amounts of trehalose in their bodies which maintains the integrity of cell membranes or organelles 19 . However, it has been reported that cryoprotectants increase the birth rate from dried spermatozoa as well as the success rate of somatic cell cloning 17 , 18 , 20 24 , spermatozoa and cells used in these studies were no longer viable following the drying treatment even in the presence of trehalose, and the cell membranes were largely damaged 3 . However, it may be argued that preserving the integrity of the DNA of FD spermatozoa is more important than maintaining the viability of sperm.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the birth rate of embryos fertilized with FD sperm was largely decreased compared with that of embryos fertilized with fresh spermatozoa due to DNA damage [29]. Kusakabe suggested that DNA damage was induced by mechanical or oxidative stress not only during freeze-drying but also during long-term preservation [30]. Kaneko et al .…”
Section: Discussionmentioning
confidence: 99%
“…) [ 83 , 84 , 85 ]. Furthermore, short-term storage [ 86 ] and worldwide transportation at ambient temperatures [ 87 ] are also possible. A similar simple sperm preservation method using evaporation has been investigated in the mouse [ 88 ].…”
Section: Simple Gamete Preservation By Freeze-drying Spermmentioning
confidence: 99%